2016
DOI: 10.1111/1467-8489.12159
|View full text |Cite
|
Sign up to set email alerts
|

Antipodean agricultural and resource economics at 60: risk and uncertainty

Abstract: Risk and uncertainty issues have been long addressed by members of AARES, reflecting the importance of the issue in agriculture, particularly in Australia. Members have been among the most innovative developers of methods and insights, around the world, as is reflected in the many publications in journals beyond the domestic shores. It seems, given the recent keen attention to such issues in the Australian literature and beyond, that, with high probability, members will continue to make strong contributions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…The study of the whole set of issues of specialization of sugar beet production showed that its state in both the country and in the regional aspects does not meet the modern requirements of the spatial location of the territorial-production beet sugar complex in the market and natural environment. Specialization of beet-sowing farms in the market is in conflict with natural factors [6]. Therefore, rational use of the resource po-tential and cost-effective production, natural and socioeconomic conditionality of the location of the sugar producing industries are not ensured [20].…”
Section: Practical Significance Suggestions and Results Ofmentioning
confidence: 99%
“…The study of the whole set of issues of specialization of sugar beet production showed that its state in both the country and in the regional aspects does not meet the modern requirements of the spatial location of the territorial-production beet sugar complex in the market and natural environment. Specialization of beet-sowing farms in the market is in conflict with natural factors [6]. Therefore, rational use of the resource po-tential and cost-effective production, natural and socioeconomic conditionality of the location of the sugar producing industries are not ensured [20].…”
Section: Practical Significance Suggestions and Results Ofmentioning
confidence: 99%
“…Publications on this topic have remained reasonably stable in quantity since then. Similarly, uncertainty and risk have been of high interest to agricultural, resource and environmental economists throughout the period (Quiggin and Anderson ), producing a number of highly cited papers (see Table S1). ‘Time series, forecasting’ and ‘Policy’ are relatively generic topics, including studies of many different commodities, products and resources, so it is perhaps unsurprising that there was no marked trend in publication numbers for either.…”
Section: Resultsmentioning
confidence: 99%
“…The existence of political affiliation can help firms to obtain more government subsidies or even direct orders, which enables them to continue to survive at a lower level of innovation even in the face of fierce market competition, so they will not have a sense of crisis and naturally will not innovate. In addition to this some politically connected firms will overinvest and induce the risk of overcapacity in order to cater for the needs of local officials to promote local economic growth, thus sacrificing the long-term development capability of the firm Li Jian et al [19]; Xu Yekun et al [20].Besides Quiggin and Anderson's study [21] presents that the uncertainty brought by economic policies has an important impact on agricultural decision-making , corporate innovation is a high-cost, long-cycle, high-risk investment decision-making activities, companies will worry that the future benefits of R & D investment will not be enough to offset the losses brought by the uncertainty of the economic policy, so in the case of fluctuating economic policies the conservative attitude of the enterprise is likely to make the innovation project is shelved Therefore, in the case of economic policy volatility, firms' conservative attitude is likely to put innovation projects on hold, which is not conducive to innovation. In addition, economic policy uncertainty worsens the external financing environment, increasing the information asymmetry between borrowers and lenders, making future cash flows more unstable and increasing the risk of default.…”
Section: Internal and External Factors Inhibit Corporate Innovationmentioning
confidence: 99%